The relationship between knowledge and attitudes toward the intention of women of reproductive age to undergo VIA examination - Elita Elita; Megawati Megawati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Cervical cancer is one of the leading causes of cancer-related mortality among women in Indonesia. Early detection through Visual Inspection with Acetic Acid (VIA) screening is a simple, effective, and affordable method to reduce cervical cancer incidence. However, the coverage of VIA screening in the working area of Kelapa Community Health Center remains low. Purpose: To analyze the relationship between knowledge and attitudes and the intention of women of reproductive age (WRA) to undergo VIA screening. Methods: This study employed a quantitative analytic design with a cross-sectional approach. The population consisted of women of reproductive age (30–50 years) in the working area of Kelapa Community Health Center. A total of 108 respondents were selected using simple random sampling. Data were collected using a structured questionnaire and analyzed using the Chi-square test with a significance level of α = 0.05. Results: The results showed a significant relationship between knowledge and intention to undergo VIA screening (p = 0.000; POR = 40.000; 95% CI: 13.18–121.39). A significant association was also found between attitudes and intention (p = 0.000; POR = 53.714; 95% CI: 16.80–171.72). Women with poor knowledge and negative attitudes were significantly more likely to have low intention to undergo VIA screening. Conclusion: Knowledge and attitudes significantly influence the intention of women of reproductive age to undergo VIA screening. Strengthening health education and promotive interventions related to cervical cancer screening is essential to increase women’s participation in VIA examinations at the primary healthcare level.